The relationship between resource acquisition methods and firm performance in Chinese new ventures: the intermediate effect of learning capability - Li Cai; Mathew Hughes; Miaomiao Yin (2014)
Despite the omnipresent popularity of the resource-based view of the firm, our understanding of how firms convert resource acquisition into performance returns remains something of a black box. We seek to unpack this problem in this study. Building on the resource-based view and combining insights from organizational learning theory, this paper develops a theoretical model consisting of seven hypotheses in which resource purchase, resource attraction, and resource internal development are positively related to new venture performance, and in which learning capability mediates these relationships. We also posit that resource acquisition methods augment the learning capability of the firm en route to securing superior new venture performance. We test these hypotheses using survey data from new ventures in China. The results indicate that all three methods of resource acquisition have positive effects on new venture performance, that resource attraction and internal development have positive effects on learning capability in new ventures, and that learning capability mediates the relationship between these two resource acquisition practices and new venture performance. We put forward implications for theory and practice to close the work.